ELLIPSES. - Fields, Noa Micaela (Anomaly: International Journal of Art & Literature, 2025)
The poem "ELLIPSES" by Noa Micaela Fields is presented. First Line: Whores, let's bewilder our many verbs; Last Line: nourishing faggotry.